Sport Concussion Assessment Tool: baseline and clinical reference limits for concussion diagnosis and management in elite Rugby Union - Tucker, R.; Falvey, E. C.; Fuller, G. W.; Hislop, M. D.; Patricios, J.; Raftery, M. (Journal of Science and Medicine in Sport, 2021)
Objectives: Rugby Union has adapted the Sports Concussion Assessment Tool (SCAT) into an abridged off-field concussion screen and the complete SCAT is used during diagnostic screens performed after head impact events. No firm guidelines exist as to what should be considered "abnormal" and warrant further evaluation. This study evaluates SCAT performances in 13,479 baseline SCAT assessments, and proposes clear reference limits for each sub-component of the SCAT5. Baseline reference limits are proposed to guide management of baseline testing by identifying abnormal sub-tests, enhancing the clinical validity of baseline screens, while clinical reference limits are identified to support concussion diagnosis when no baseline is available.